(3MGTjI Ydi eYGde GdOjfs - (3SdWGf GdYdeGA, SdWGf GdYdeGA, MSjf Hf eMeO GdejQRG QajY GdOjf, J (B1064(3g` (B1654(3es ((3MSf Hf eMeO GdEjQhGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3GdebOeI aj eQJHI GdOYhi Hd Yjf GdeOYj acdG fQjO aj gPG GdHjGf (B... (3fYe dh cGfJ GdebOeGJ GdSGHbI XGgQI jecf LYdgGs
(3BNQgG (B:s
(3BNQgG(B: (3jLhR GdaJhi eeG jMJed GdJChjd dG jNai Cf GMJeGd GdJChjd eTJQc EP GdaQV JSGhjgeG aj LejY GdCehQ Shi eNGdaI GdYdGeI hehGabJgG aGMJeGd GdJbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 256s
(3GdPQjYI, L (B6: 150s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs